ANALISIS PENDAPATAN USAHATANI BAWANG DAUN DI DESA SINSINGON KECAMATAN PASSI TIMUR KABUPATEN BOLAANG MONGONDOW - Leslyanti Agatha Welang; Gene Henfried Meyer Kapantow; Benny Adrian Berthy Sagay (Sam Ratulangi University, 2020)
This study aims to analyze the income of leek farming. This research was conducted in Sinsingon Village, Passi Timur District, Bolaang Mongondow Regency. This research lasted for 3 months from November 2018 to January 2019. Sampling in this study was carried out by simple random sampling, as many as 30 farmers. Primary data collection used in this study using survey methods by means of direct interviews with the help of questionnaires. Secondary data were obtained by the Sinsingon Village office. Analysis of the data used in this research is descriptive analysis and is presented in tabular form. To see the level of economic benefits of scallions will be used analysis of revenue, costs, income, then proceed with the analysis of the return cost ratio. The results showed that the the average revenue of leek farming per farmer is Rp. 24,400,020 per planting season and the total average cost per farmer is Rp. 11,229,083, resulting in an average income per farmer of Rp. 13,170,937 per growing sesion. The R / C was 2.17 which that the onion farming in Sinsingon Village, Passi Timur District was profitable.*eprm